A wear-resistant and strong grip new energy vehicle tread rubber and preparation method thereof
By using modified polyimide fiber and three-stage vulcanization process in tire tread glue, the problem that existing tread glue is difficult to meet wear resistance, slippage and low rolling resistance at the same time is solved, and the overall performance of tread glue is improved and driving safety is improved.
Patent Information
- Application Number
- CN202411201541.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-08-29
AI Technical Summary
Existing tire tread glue is difficult to meet wear resistance, slippage and low rolling resistance at the same time, resulting in a decrease in other properties when one performance is improved.
A tread glue formula including polystyrene butadiene rubber, natural rubber, reinforced resin fiber, white carbon black, carbon black, zinc oxide, stearic acid, anti-aging agent, sulfur, accelerator and anti-coke agent is adopted, and modified polyimide fiber is prepared by electrospinning method, combined with the three-stage vulcanization process to improve the overall performance of the tread glue.
It significantly improves the wear resistance, rolling resistance and grip of the tread glue, ensures that the performance of the tires on wet and dry ground is improved, and the driving safety factor is improved.
Smart Images

Figure BDA0005017964180000081 
Figure BDA0005017964180000101 
Figure BDA0005017964180000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of tire manufacturing, and in particular to a wear-resistant, high-grip new energy vehicle tread rubber and a preparation method thereof. Background Art
[0002] As one of the most important components of a car, tires mainly support the entire weight of the vehicle, bear the load of the car, transmit traction and braking torque, and ensure the adhesion between the wheel and the road surface. The use of tires is easily affected by temperature, road conditions, etc. The tire tread rubber is in direct contact with the road surface, so the tread rubber is required to have excellent wet braking performance, wear resistance, weather resistance, etc.
[0003] In recent years, "green tires" have attracted widespread attention due to their good elasticity, low rolling resistance, anti-slip and high wear resistance, and the automotive market has become more and more urgent in demand for "green tires". However, it is difficult to meet the low rolling resistance, high wear resistance, anti-slip and other properties of tires at the same time. For example, the current low rolling resistance tread rubber, although it has low rolling resistance, has the disadvantages of non-wear resistance of the rubber and poor grip performance. If the dry grip is improved, the wear resistance decreases rapidly. Therefore, how to ensure the wear resistance, anti-slip, low rolling resistance and other properties of the tire tread rubber at the same time has become the current research focus of tire tread rubber.
[0004] The existing technology mainly improves the wear performance of the rubber composition by improving the structure of the reinforcing agent in the rubber composition and improving the combination of the rubber body and the reinforcing agent; or by modifying the main rubber to enhance the combination of the rubber and the reinforcing agent to improve the performance of the rubber composition. However, when the above method improves one performance, other performances will decrease, and it is still impossible to simultaneously improve the wear resistance, anti-slip and low rolling resistance of the tread rubber.
[0005] Therefore, it is necessary to improve the existing tire tread rubber and develop a wear-resistant, grip-strong new energy vehicle tread rubber and a preparation method thereof. Summary of the invention
[0006] In view of the above situation, in order to make up for the defects of the prior art, the present invention provides a wear-resistant and high-grip new energy vehicle tread rubber and a preparation method thereof, which at least solves some of the problems of the prior art.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] On the one hand, a wear-resistant and grip-strong new energy vehicle tread rubber comprises the following raw materials in parts by weight:
[0009] 65-85 parts of solution-polymerized styrene-butadiene rubber, 15-35 parts of natural rubber, 8-15 parts of reinforcing resin fiber, 15-20 parts of white carbon black, 5-10 parts of carbon black, 2-5 parts of zinc oxide, 2-5 parts of stearic acid, 1-3 parts of antioxidant, 0.1-2 parts of sulfur, 0.5-2 parts of accelerator, 0.1-2 parts of scorch retarder; wherein,
[0010] The reinforced resin fiber is prepared by using N,N-diethyl-2-butene-1,4-diamine and p-aminodiphenylamine as diamine monomers, phenylsuccinic anhydride and pyromellitic anhydride as anhydride monomers, and then using an electrostatic spinning method to generate a resin through polycondensation.
[0011] Preferably, the wear-resistant and high-grip new energy vehicle tread rubber includes the following raw materials by weight: 75-80 parts of solution-polymerized styrene-butadiene rubber, 20-25 parts of natural rubber, 10-12 parts of reinforcing resin fiber, 17-20 parts of white carbon black, 6-8 parts of carbon black, 3-4 parts of zinc oxide, 2-4 parts of stearic acid, 2-3 parts of antioxidant, 1-2 parts of sulfur, 1-2 parts of accelerator, and 0.5-1 part of scorch retarder.
[0012] In some specific embodiments, the reinforced resin fiber is prepared by the following method:
[0013] The diamine monomer is dissolved in a sufficient amount of NMP, and then the anhydride monomer is added, refluxed at 15-20°C for 5-6 hours, and then the temperature is raised to 160-180°C for condensation reaction for 6-8 hours to obtain a spinning solution, which is then electrospun to obtain modified polyimide fibers.
[0014] Furthermore, in the process of preparing the reinforced resin fiber, the diamine monomer comprises N,N-diethyl-2-butene-1,4-diamine and p-aminodiphenylamine in a molar ratio of 10:(2-5); preferably, the diamine monomer comprises N,N-diethyl-2-butene-1,4-diamine and p-aminodiphenylamine in a molar ratio of 10:(3.2-4).
[0015] Furthermore, during the preparation of the reinforced resin fiber, the anhydride monomer comprises phenylsuccinic anhydride and pyromellitic anhydride in a molar ratio of 1:(2-3); preferably, the anhydride monomer comprises phenylsuccinic anhydride and pyromellitic anhydride in a molar ratio of 1:(2.5-2.7).
[0016] Furthermore, during the preparation of the reinforced resin fiber, the molar ratio of the diamine monomer to the anhydride monomer is 1:(1-1.1).
[0017] In some specific embodiments, the antioxidant includes but is not limited to at least one of antioxidant DNP, antioxidant 4020, antioxidant TMQ, and antioxidant BLE.
[0018] In some specific embodiments, the accelerator is selected from at least one of dithiocarbamate accelerators, aldehyde amine accelerators, thiuram accelerators, sulfonamide accelerators, thiazole accelerators and xanthate accelerators.
[0019] In some specific embodiments, the scorch retarder includes but is not limited to at least one of N-nitrosodiphenylamine, N-nitroso-N-phenyl-1-naphthylamine, nitroso-2,2,4-trimethyl-1,2-dihydroquinoline polymer, 1,3-dichloro-5,5-dimethylhydantoin, diphenylsilanediol, and hexaisopropylthiomelamine.
[0020] In a further embodiment, a surfactant is added to the wear-resistant and grip-strong new energy vehicle tread rubber, and the added amount of the surfactant is 1 to 2.5% of the total mass of the rubber; the surfactant is calcium lignin sulfonate and glycerol fatty acid ester in a mass ratio of 1: (0.2 to 0.3).
[0021] Preferably, the glycerol fatty acid ester is selected from at least one of glycerol stearate citrate, glycerol stearate lactate and glycerol stearate succinate.
[0022] On the other hand, a method for preparing a wear-resistant and grip-strong new energy vehicle tread rubber comprises the following steps:
[0023] (1) mixing solution polymerized styrene-butadiene rubber, natural rubber and reinforcing resin fiber to obtain an initial masterbatch;
[0024] (2) mixing the initial masterbatch with white carbon black, carbon black, stearic acid, zinc oxide, an antioxidant, a scorch retarder, sulfur and an accelerator to obtain a rubber mixture;
[0025] (3) The mixed rubber is vulcanized in sections to obtain a wear-resistant and grip-strong new energy vehicle tread rubber.
[0026] Furthermore, in step (1), the mixing temperature is 120 to 150° C. and the mixing time is 50 to 100 seconds.
[0027] Furthermore, in step (2), the mixing temperature is 130 to 150° C. and the mixing time is 100 to 200 seconds.
[0028] Furthermore, in step (3), the step of segmented vulcanization is:
[0029] One-stage vulcanization: vulcanization temperature is 100-110°C, pressure is 8-10Mpa, and time is 20-40s;
[0030] Second stage vulcanization: vulcanization temperature is 130-135°C, pressure is 12-13Mpa, and time is 30-50s;
[0031] Three-stage and six-stage vulcanization: vulcanization temperature is 110-120°C, pressure is 9-11Mpa, and time is 20-40s.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The present invention provides a wear-resistant and high-grip new energy vehicle tread rubber. Under the premise of ensuring good mechanical properties, the wear resistance, rolling resistance, and dry and wet grip of the tread rubber are greatly improved. The tire made of the tread rubber has excellent wear resistance and grip, and has a high driving safety factor.
[0034] 2. The present invention adds reinforcing resin fiber - modified polyimide fiber to the tread rubber material. Compared with conventional polyimide fibers, phenylsuccinic anhydride and N,N-diethyl-2-butene-1,4-diamine are introduced into the polyimide molecules of the modified polyimide fibers, which reduces the polarity of the polyimide molecular chain and improves the compatibility with rubber, thereby compensating for the defect of poor dispersibility of existing polyamide fibers. The present invention can effectively enhance the strength and wear resistance of the tread rubber, and can also ensure that the hardness of the rubber is not too high, thereby improving the grip ability and the anti-skid performance.
[0035] 3. The present invention adds surfactants calcium lignin sulfonate and glycerol fatty acid ester to the tread rubber material. Compared with other surfactants, the addition of these two surfactants helps the components in the tread rubber to cooperate with each other and work together, which can not only greatly reduce the rolling resistance during driving, but also improve the grip on dry and wet lands.
[0036] 4. The present invention adopts three-stage vulcanization in the process of preparing the tread rubber, which helps to make the performance of the vulcanized rubber uniform and improve the comprehensive performance of the tread rubber. DETAILED DESCRIPTION
[0037] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is only an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the invention of the present invention based on the disclosed content, and they should also fall within the scope of the present invention.
[0038] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.
[0039] Example 1
[0040] A wear-resistant and grip-strong new energy vehicle tread rubber, comprising the following raw materials in parts by weight:
[0041] 65 parts of solution-polymerized styrene-butadiene rubber, 35 parts of natural rubber, 8 parts of reinforcing resin fiber, 20 parts of white carbon black, 10 parts of carbon black, 2 parts of zinc oxide, 2 parts of stearic acid, 1 part of antioxidant 4020, 0.1 parts of sulfur, 0.5 parts of accelerator CZ, and 0.1 parts of scorch retarder N-nitrosodiphenylamine.
[0042] Wherein, the reinforcing resin fiber is a modified polyimide fiber, which is prepared by the following method:
[0043] The diamine monomer (N,N-diethyl-2-butene-1,4-diamine and p-aminodiphenylamine in a molar ratio of 10:2) was dissolved in a sufficient amount of NMP, and then anhydride monomer (phenylsuccinic anhydride and pyromellitic anhydride in a molar ratio of 1:2) was added, the molar ratio of the diamine monomer to the anhydride monomer was 1:1.1, and the reaction was refluxed at 15°C for 6 hours, and then the temperature was raised to 160°C for condensation reaction for 8 hours to obtain a spinning solution, which was then electrospinned to obtain modified polyimide fibers.
[0044] The method for preparing the above-mentioned wear-resistant and high-grip new energy vehicle tread rubber comprises the following steps:
[0045] (1) mixing solution polymerized styrene-butadiene rubber, natural rubber and reinforcing resin fiber for 100 seconds at a mixing temperature of 120° C. to obtain an initial masterbatch;
[0046] (2) mixing the initial masterbatch with white carbon black, carbon black, stearic acid, zinc oxide, antioxidant, anti-scorch agent, sulfur and accelerator for 200 seconds at a mixing temperature of 130° C. to obtain a mixed rubber;
[0047] (3) vulcanizing the mixed rubber in sections to obtain a wear-resistant and grip-strong new energy vehicle tread rubber; the steps of the section vulcanization are:
[0048] One stage vulcanization: vulcanization temperature 110℃, pressure 8Mpa, time 40s;
[0049] Second stage vulcanization: vulcanization temperature is 135℃, pressure is 13Mpa, time is 30s;
[0050] Three-stage and six-stage vulcanization: vulcanization temperature is 120℃, pressure is 11Mpa, and time is 40s.
[0051] Example 2
[0052] Another wear-resistant and grip-strong new energy vehicle tread rubber comprises the following raw materials in parts by weight:
[0053] 75 parts of solution-polymerized styrene-butadiene rubber, 25 parts of natural rubber, 10 parts of reinforcing resin fiber, 20 parts of white carbon black, 8 parts of carbon black, 3 parts of zinc oxide, 2 parts of stearic acid, 2 parts of antioxidant DNP, 1 part of sulfur, 1 part of accelerator CZ, and 0.5 parts of scorch retarder N-nitroso-N-phenyl-base-naphthylamine.
[0054] Wherein, the reinforcing resin fiber is a modified polyimide fiber, which is prepared by the following method:
[0055] The diamine monomer (N,N-diethyl-2-butene-1,4-diamine and p-aminodiphenylamine in a molar ratio of 10:3.2) was dissolved in a sufficient amount of NMP, and then anhydride monomer (phenylsuccinic anhydride and pyromellitic anhydride in a molar ratio of 1:2.5) was added. The molar ratio of the diamine monomer to the anhydride monomer was 1:1.1. The reaction was refluxed at 15°C for 6 hours, and then the temperature was raised to 160°C for condensation reaction for 8 hours to obtain a spinning solution, which was then electrospinned to obtain modified polyimide fibers.
[0056] The method for preparing the above-mentioned wear-resistant and high-grip new energy vehicle tread rubber comprises the following steps:
[0057] (1) mixing solution polymerized styrene-butadiene rubber, natural rubber and reinforcing resin fiber for 100 seconds at a mixing temperature of 150° C. to obtain an initial masterbatch;
[0058] (2) mixing the initial masterbatch with white carbon black, carbon black, stearic acid, zinc oxide, antioxidant, anti-scorch agent, sulfur and accelerator for 100 seconds at a mixing temperature of 150° C. to obtain a mixed rubber;
[0059] (3) vulcanizing the mixed rubber in sections to obtain a wear-resistant and grip-strong new energy vehicle tread rubber; the steps of the section vulcanization are:
[0060] One stage vulcanization: vulcanization temperature 110℃, pressure 8Mpa, time 40s;
[0061] Second stage vulcanization: vulcanization temperature is 135℃, pressure is 13Mpa, time is 30s;
[0062] Three-stage and six-stage vulcanization: vulcanization temperature is 120℃, pressure is 11Mpa, and time is 40s.
[0063] Example 3
[0064] A wear-resistant and grip-strong new energy vehicle tread rubber, comprising the following raw materials in parts by weight:
[0065] 80 parts of solution-polymerized styrene-butadiene rubber, 20 parts of natural rubber, 12 parts of reinforcing resin fiber, 17 parts of white carbon black, 6 parts of carbon black, 3 parts of zinc oxide, 4 parts of stearic acid, 3 parts of antioxidant DNP, 2 parts of sulfur, 2 parts of accelerator CZ, and 1 part of scorch retarder N-nitroso-N-phenyl-base-naphthylamine.
[0066] Wherein, the reinforcing resin fiber is a modified polyimide fiber, which is prepared by the following method:
[0067] The diamine monomer (N,N-diethyl-2-butene-1,4-diamine and p-aminodiphenylamine in a molar ratio of 10:4) was dissolved in a sufficient amount of NMP, and then anhydride monomer (phenylsuccinic anhydride and pyromellitic anhydride in a molar ratio of 1:2.7) was added. The molar ratio of the diamine monomer to the anhydride monomer was 1:1.1. The reaction was refluxed at 20°C for 5 hours, and then the temperature was raised to 180°C for condensation reaction for 6 hours to obtain a spinning solution, which was then electrospinned to obtain modified polyimide fibers.
[0068] The method for preparing the above-mentioned wear-resistant and high-grip new energy vehicle tread rubber comprises the following steps:
[0069] (1) mixing solution polymerized styrene-butadiene rubber, natural rubber and reinforcing resin fiber for 100 seconds at a mixing temperature of 150° C. to obtain an initial masterbatch;
[0070] (2) mixing the initial masterbatch with white carbon black, carbon black, stearic acid, zinc oxide, antioxidant, anti-scorch agent, sulfur and accelerator for 100 seconds at a mixing temperature of 150° C. to obtain a mixed rubber;
[0071] (3) vulcanizing the mixed rubber in sections to obtain a wear-resistant and grip-strong new energy vehicle tread rubber; the steps of the section vulcanization are:
[0072] One stage vulcanization: vulcanization temperature 110℃, pressure 8Mpa, time 40s;
[0073] Second stage vulcanization: vulcanization temperature is 135℃, pressure is 13Mpa, time is 30s;
[0074] Three-stage and six-stage vulcanization: vulcanization temperature is 120℃, pressure is 11Mpa, and time is 40s.
[0075] Example 4
[0076] A wear-resistant and grip-strong new energy vehicle tread rubber, comprising the following raw materials in parts by weight:
[0077] 85 parts of solution-polymerized styrene-butadiene rubber, 15 parts of natural rubber, 15 parts of reinforcing resin fiber, 15 parts of white carbon black, 5 parts of carbon black, 5 parts of zinc oxide, 5 parts of stearic acid, 3 parts of antioxidant DNP, 2 parts of sulfur, 2 parts of accelerator CZ, and 2 parts of scorch retarder N-nitroso-N-phenyl-base-naphthylamine.
[0078] Wherein, the reinforcing resin fiber is a modified polyimide fiber, which is prepared by the following method:
[0079] The diamine monomer (N,N-diethyl-2-butene-1,4-diamine and p-aminodiphenylamine in a molar ratio of 10:5) was dissolved in a sufficient amount of NMP, and then anhydride monomer (phenylsuccinic anhydride and pyromellitic anhydride in a molar ratio of 1:3) was added. The molar ratio of the diamine monomer to the anhydride monomer was 1:1.1. The reaction was refluxed at 20°C for 5 hours, and then the temperature was raised to 180°C for condensation reaction for 6 hours to obtain a spinning solution, which was then electrospun to obtain modified polyimide fibers.
[0080] The method for preparing the above-mentioned wear-resistant and high-grip new energy vehicle tread rubber comprises the following steps:
[0081] (1) mixing solution polymerized styrene-butadiene rubber, natural rubber and reinforcing resin fiber for 100 seconds at a mixing temperature of 150° C. to obtain an initial masterbatch;
[0082] (2) mixing the initial masterbatch with white carbon black, carbon black, stearic acid, zinc oxide, antioxidant, anti-scorch agent, sulfur and accelerator for 100 seconds at a mixing temperature of 150° C. to obtain a mixed rubber;
[0083] (3) vulcanizing the mixed rubber in sections to obtain a wear-resistant and grip-strong new energy vehicle tread rubber; the steps of the section vulcanization are:
[0084] One stage vulcanization: vulcanization temperature 100℃, pressure 10Mpa, time 20s;
[0085] Second stage vulcanization: vulcanization temperature is 130℃, pressure is 12Mpa, time is 50s;
[0086] Three-stage and six-stage vulcanization: vulcanization temperature is 110℃, pressure is 9Mpa, and time is 20s.
[0087] Embodiment 5-8
[0088] The difference between this embodiment and embodiment 2 is that the ratio of diamine monomer or acid anhydride monomer in the preparation process of the reinforced resin fiber is different, and the total amount of diamine monomer or acid anhydride monomer remains unchanged, as shown in the following Table 1.
[0089] Table 1
[0090]
[0091] Example 9
[0092] The difference between this embodiment and embodiment 2 is that 1 part of calcium lignin sulfonate and glyceryl stearate citrate in a mass ratio of 1:0.2 are further added to the wear-resistant and grip-strong new energy vehicle tread rubber, and the other components remain unchanged.
[0093] Example 10
[0094] The difference between this embodiment and embodiment 2 is that the wear-resistant and grip-strong new energy vehicle tread rubber further comprises 2.5 parts of calcium lignin sulfonate and glyceryl stearate succinate in a mass ratio of 1:0.3, and the other components remain unchanged.
[0095] Embodiment 11
[0096] The difference between this embodiment and embodiment 2 is that the wear-resistant and grip-strong new energy vehicle tread rubber further comprises 2.5 parts of calcium lignin sulfonate, and the other components remain unchanged.
[0097] Example 12
[0098] The difference between this embodiment and embodiment 2 is that the wear-resistant and grip-strong new energy vehicle tread rubber further comprises 2.5 parts of glyceryl stearate succinate, and the other components remain unchanged.
[0099] Example 13
[0100] The difference between this embodiment and embodiment 10 is that glyceryl stearate succinate is replaced by an equal amount of fatty alcohol polyoxyethylene ether (AEO-9), and the other components remain unchanged.
[0101] Comparative Example 1
[0102] The difference between this comparative example and Example 2 is that, during the preparation of the reinforced resin fiber, the diamine monomer is only N,N-diethyl-2-butene-1,4-diamine, and the total amount of the diamine monomer remains unchanged.
[0103] Comparative Example 2
[0104] The difference between this comparative example and Example 2 is that, during the preparation of the reinforced resin fiber, the acid anhydride monomer is only pyromellitic anhydride, and the total amount of the acid anhydride monomer remains unchanged.
[0105] Comparative Example 3
[0106] The difference between this comparative example and Example 2 is that, during the preparation of the reinforced resin fiber, the diamine monomer is N,N-diethyl-2-butene-1,4-diamine, the anhydride monomer is pyromellitic anhydride, and the total amounts of the diamine monomer and the anhydride monomer remain unchanged.
[0107] Comparative Example 4
[0108] The difference between this comparative example and Example 2 is that no reinforcing resin fiber is added to the wear-resistant and grip-strong new energy vehicle tread rubber.
[0109] Comparative Example 5
[0110] The difference between this comparative example and Example 2 is that, during the preparation process of the wear-resistant and grip-strong new energy vehicle tread rubber, only one vulcanization stage is performed, and the vulcanization temperature is 135° C., the pressure is 13 MPa, and the time is 30 s.
[0111] Test Example 1
[0112] The mechanical properties of the tread rubbers prepared in the above embodiments and comparative examples were tested, and the results are shown in Table 2 below.
[0113] Table 2
[0114] Group Tensile strength, MPa 100% tensile stress, MPa 300% tensile stress, MPa Elongation at break, % Example 1 29.7 4.0 13.2 556.7 Example 2 30.5 4.3 14.0 584.5 Example 3 30.3 4.2 13.8 579.4 Example 4 30.0 4.0 13.5 572.1 Example 5 26.0 3.2 13.0 570.5 Example 6 26.9 3.5 13.5 568.8 Example 7 27.4 3.2 13.6 576.1 Example 8 27.8 2.6 13.3 577.4 Example 9 30.4 4.7 15.4 578.6 Example 10 30.3 4.8 15.6 580.1 Embodiment 11 29.6 3.9 13.3 580.4 Example 12 29.8 4.1 13.7 577.2 Example 13 29.1 3.9 13.1 581.2 Comparative Example 1 23.0 2.6 9.6 528.7 Comparative Example 2 22.4 2.6 9.8 520.1 Comparative Example 3 22.2 2.2 8.7 525.4 Comparative Example 4 20.7 2.2 8.0 508.6 Comparative Example 5 23.1 2.5 9.1 556.8 Test Standards GB / T 529-2008 GB / T 39693.7-2022 GB / T 528-2009 GB / T1687-2016
[0115] As shown in the table, the tread rubber prepared by the present invention has excellent mechanical properties. Comparison of Example 2 and Comparative Examples 1-4 shows that, compared with conventional polyimide resin fibers, the mechanical properties of the tread rubber added with the modified polyimide resin fibers of the present invention are improved.
[0116] Test Example 2
[0117] The tread rubbers prepared in the above embodiments and comparative examples were subjected to wear resistance tests, and the test standard was based on GB / T1689-2014 Determination of wear resistance of vulcanized rubber (using an Akron abrasion machine). The results are shown in Table 3 below.
[0118] Table 3
[0119]
[0120]
[0121] As shown in the table, it is known that the smaller the Akron wear, the better the wear resistance. The Akron wear of the tread rubber prepared by the present invention is low and has excellent wear resistance. However, the Akron wear in Comparative Examples 1-4 is significantly higher than that in Example 2, and the wear resistance is poor, indicating that the addition of modified polyimide fiber helps to improve the wear resistance of the tread rubber. It can also be seen that the Akron wear of Examples 9 and 10 is lower than that of Example 2, indicating that the addition of surfactant helps to further improve the wear resistance of the tread rubber.
[0122] Test Example 3
[0123] A dynamic mechanical analyzer VR-7120 was used for dynamic analysis test (DMA), and the test conditions were as follows: tensile mode; frequency, 12 Hz; static strain 7%, dynamic strain 0.25%; temperature rise, 2°C / min.
[0124] DMA is an important method for testing the mechanical properties and viscoelastic properties of materials. It uses tanδ and E' at different temperatures to characterize the dynamic viscoelastic properties of rubber compositions. Usually, the hysteresis loss factor tanδ at 0°C is used to characterize the wet grip performance of the rubber compound. The larger the value, the better the wet grip performance of the rubber composition. The hysteresis loss factor tanδ at 20°C characterizes the dry grip performance of the rubber compound. The larger the value, the better the dry grip performance of the rubber composition. The tanδ value at 60°C characterizes the rolling resistance of the vulcanized rubber. The lower the value, the lower the rolling resistance. The elastic modulus E' at 0°C characterizes the wet handling performance of the rubber compound. Similarly, the larger the value, the better the handling performance of the rubber composition.
[0125] The test results are shown in Table 4 below.
[0126] Table 4
[0127]
[0128]
[0129] The results show that the rubber composition has a tanδ value of more than 0.7 at 0°C, a tanδ value of more than 0.5 at 20°C, and an E' value of more than 18 at 20°C, indicating that it has excellent wet grip performance and dry grip performance, as well as good handling performance.
[0130] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A wear-resistant and strong grip new energy vehicle tread rubber, characterized in that: The following raw materials are included by weight: 65-85 parts of solution-polymerized styrene-butadiene rubber, 15-35 parts of natural rubber, 8-15 parts of reinforcing resin fiber, 15-20 parts of white carbon black, 5-10 parts of carbon black, 2-5 parts of zinc oxide, 2-5 parts of stearic acid, 1-3 parts of antioxidant, 0.1-2 parts of sulfur, 0.5-2 parts of accelerator, 0.1-2 parts of scorch retarder; wherein, The reinforced resin fiber is prepared by the following method: The diamine monomer is dissolved in a sufficient amount of NMP, and then an anhydride monomer is added, and the reaction is refluxed at 15-20° C. for 5-6 hours, and then the temperature is raised to 160-180° C. for polycondensation reaction for 6-8 hours to obtain a spinning solution, and then the modified polyimide fiber is obtained by electrospinning; The diamine monomer comprises N,N-diethyl-2-butene-1,4-diamine and p-aminodiphenylamine in a molar ratio of 10:(2-5); the acid anhydride monomer comprises phenylsuccinic anhydride and pyromellitic anhydride in a molar ratio of 1:(2-3); the molar ratio of the diamine monomer to the acid anhydride monomer is 1:(1-1.1).
2. The wear-resistant and grip-strong new energy vehicle tread rubber according to claim 1, characterized in that: Calculated by weight, the raw materials include: 75-80 parts of solution-polymerized styrene-butadiene rubber, 20-25 parts of natural rubber, 10-12 parts of reinforcing resin fiber, 17-20 parts of white carbon black, 6-8 parts of carbon black, 3-4 parts of zinc oxide, 2-4 parts of stearic acid, 2-3 parts of antioxidant, 1-2 parts of sulfur, 1-2 parts of accelerator and 0.5-1 part of scorch retarder.
3. The wear-resistant and grip-strong new energy vehicle tread rubber according to claim 1, characterized in that: The molar ratio of N,N-diethyl-2-butene-1,4-diamine to p-aminodiphenylamine in the reinforcing resin fiber is 10:(3.2-4); the molar ratio of phenylsuccinic anhydride to pyromellitic anhydride is 1:(2.5-2.7).
4. The wear-resistant and grip-strong new energy vehicle tread rubber according to any one of claims 1 to 3, characterized in that: The wear-resistant and high-grip new energy vehicle tread rubber also contains a surfactant, which is calcium lignin sulfonate and glycerol fatty acid ester in a mass ratio of 1: (0.2-0.3).
5. The wear-resistant and grip-strong new energy vehicle tread rubber according to claim 4, characterized in that: The glycerol fatty acid ester is selected from at least one of glycerol stearate citrate, glycerol stearate lactate, and glycerol stearate succinate.
6. The method for preparing the wear-resistant and high-grip new energy vehicle tread rubber according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) mixing solution polymerized styrene-butadiene rubber, natural rubber and reinforcing resin fiber to obtain an initial masterbatch; (2) mixing the initial masterbatch with white carbon black, carbon black, stearic acid, zinc oxide, an antioxidant, and a scorch retarder to obtain a rubber mixture; (3) The mixed rubber is mixed with sulfur and an accelerator and vulcanized in stages to obtain a wear-resistant and grip-strong new energy vehicle tread rubber.
7. The method for preparing the wear-resistant and high-grip new energy vehicle tread rubber according to claim 6, characterized in that: In step (1), the mixing temperature is 120 to 150° C. and the mixing time is 50 to 100 seconds.
8. The method for preparing the wear-resistant and high-grip new energy vehicle tread rubber according to claim 6, characterized in that: In step (2), the mixing temperature is 130 to 150° C. and the mixing time is 100 to 200 seconds.
9. The method for preparing the wear-resistant and high-grip new energy vehicle tread rubber according to claim 6, characterized in that: In step (3), the step of segmented vulcanization is: One-stage vulcanization: vulcanization temperature is 100-110°C, pressure is 8-10Mpa, and time is 20-40s; Second stage vulcanization: vulcanization temperature is 130-135°C, pressure is 12-13Mpa, and time is 30-50s; Three-stage and six-stage vulcanization: vulcanization temperature is 110-120°C, pressure is 9-11Mpa, and time is 20-40s.
Citation Information
Patent Citations
Low-temperature-resistant and high-wet-skid-resistant snow tire tread rubber and preparation method thereof
CN112812388A
All-steel snow tire tread and preparation method thereof
CN117801385A